Heavy Smoking Patients Receiving a Lung Cancer Screen Want to Quit: A Call for Tailored Cessation Interventions - Bernstein, Michael H.; Baird, Grayson L.; Oueidat, Karim; Agarwal, Saurabh; Atalay, Alexander; Healey, Shannon; Healey, Terrance T. (Frontiers in Medicine, 2022)
Background: Lung cancer screening for current or former heavy smokers is now recommended among all asymptomatic adults 50-80 years old with a 20 pack-year history of smoking. However, little is known about the smoking-related attitudes of this population. Method: An assessment was conducted among 1472 current smokers who presented for an annual lung cancer screen at one of 12 diagnostic imaging sites in Rhode Island between April 2019 and May 2020. Patients were asked about their use of smoking products, interest in quitting, and smoking-related attitudes. Results: Patients smoked a median of 16 cigarettes per day; 86.6% were daily cigarette smokers and 30.1% were daily cigar smokers. In total, 91.4% of patients were, to some degree, interested in quitting smoking and 71.4% were seriously thinking about quitting in the next 6 months or sooner. Patients planned on smoking less regardless of whether their lung screen was positive or negative for cancer, though they were more likely to plan on smoking less if negative (on 0-3 pt Likert scale: 0.31, 95% CI [0.27, 0.34] vs. 0.77, 95% CI [0.72, 0.81]). Confidence in quitting and belief in one’s inherent ability to quit smoking varied substantially within the sample. Conclusion: Nearly all current smokers receiving a lung cancer screen have some interest in smoking cessation. Due to the heterogeneity in some smoking-related attitudes, tailored interventions for this population should be tested.